State Regulation of Undocumented African Migrants in China: A Multi-scalar Analysis. (June 2015) - Lan, Shanshan
Based on archival and ethnographic research, this paper examines the introduction, nature and implementation of a recent anti-immigrant act in Guangdong province and its implications in the regional, national and international contexts. Chinese state regulation of undocumented African migrants is analyzed with regard to the legal production of African 'illegality' in the Guangdong context; the contradictions in the implementation of the Guangdong Act and its unintended consequences; and the discrepancy between anti-African immigrant campaign at the local level and pro-African political ideology at the national and international levels.